Bank-specific, industry-specific and macroeconomic determinants of bank efficiency: empirical evidence from the Thai banking sector - Sufian, Fadzlan; Habibullah, Muzafar Shah (Sage Publications, 2010)
This paper examines the efficiency of the Thai banking sector from 1999 to 2008 by using the data envelopment analysis (DEA) method. The results indicate that inefficiency in the sector stems mainly from scale rather than pure technical efficiencies. The findings suggest that small banks are most efficient, while medium-sized banks have been the least efficient banking group. Domestic banks have been relatively more efficient than their foreign bank peers, which can be attributed largely to a higher pure technical efficiency (PTE) level. The results from the multivariate regression analysis suggest that banks with higher loans intensity and which are relatively better capitalised tend to exhibit higher efficiency levels. On the other hand, credit risk is negatively related to bank efficiency. The empirical findings suggest that the recent global financial crisis exerts a negative impact on the efficiency of Thai banks.